An interstitial deletion of chromosome 9 in a girl with multiple congenital anomalies. Issue 6 (December 1977) - Wisniewski, L; Purdy, G; Hassold, T; Wilson, C; Bentley, K; Hackel, E; Higgins, J V
Abstract : An infant with peculiar facies, coloboma of both eyes, and developmental retardation was found to have d de novo interstitial deletion of the secondary constriction and some adjacent euchromatin on one of her No. 9 chromosomes, del(9)(q11q21). Since studies on duplications, variants, and the molecular composition of the secondary constriction suggest that it contributes little if any information necessary to normal development, deletion of the euchromatin alone is most probably responsible for the clinical findings.